Reconstructive versus non-reconstructive treatment of anterior cruciate ligament insufficiency: a retrospective matched-pair long-term follow-up - Streich, Nikolaus; Zimmermann, David; Bode, Gerrit; Schmitt, Holger (International orthopaedics, 2011)
In this retrospective case series 80 patients divided in 40 matched pair groups with an arthroscopically proven ACL insufficiency were followed up for 15 years. One half was reconstructed using an autologous BTB patella graft, the other half was treated by a conservative physiotherapeutic based rehabilitation program. At follow-up the clinical scores (Lysholm, IKDC) showed no significant differences between subjects who had undergone ACL reconstruction and those who had not. Furthermore there was no detectable difference in the incidence of osteoarthritis between the cohorts. Patients having a negative pivot shift test showed significantly less signs of radiographic osteoarthritis and better functional assessment scores whether reconstructed or not. Based on these results and a review of the literature there is no clear evidence that ACL reconstruction reduces the rate of OA development or improves the long-term symptomatic outcome. Probably review of reconstruction by an anatomical approach will be more successful than operative techniques decades ago.
Online veröffentlicht: 3 Dezember 2010
Gesehen am 24.10.2022